Determination of free and total vincristine in human plasma after intravenous administration of vincristine sulfate liposome injection using ultra-high performance liquid chromatography tandem mass spectrometry - Yang, Fen; Wang, Hongyun; Liu, Ming; Hu, Pei; Jiang, Ji (Journal of Chromatography A, 2013)
► An assay for the determination of free and total vincristine (VCR) in plasma. ► The first validated method of separating free VCR from liposomes. ► The SPE method was feasible to separate free VCR without liposomal damage. ► The present method was validated according to FDA guidance. ► The method was applied to the PK studies of liposomal VCR in subjects with lymphoma. Vincristine sulfate liposome is a liposomal formulation of vincristine sulfate, a traditional anticancer drug, encapsulated in the aqueous core of phospholipid/cholesterol liposomes, which are kinds of targeted carriers to enhance malignancy targeting, exposure and anticancer activity of the drug. To evaluate and compare the pharmacokinetics of nonliposomal and liposome-encapsulated VCR and pharmacodynamic relationships associated with the toxicity and the efficacy behavior, it is essential to have a reliable method of separating the free and liposomal forms of the drug. In this paper, we have developed and validated methods to quantify the free vincristine (F-VCR) and total vincristine (T-VCR) in human plasma after intravenous administration of vincristine sulfate liposome injection (VSLI). The methods involve solid-phase extraction (SPE) for separating the F-VCR and liquid–liquid extraction (LLE) for releasing the VCR totally from the liposomal forms followed by an ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC–MS/MS) method. The detection was performed on a triple quadrupole tandem mass spectrometer in multiple reaction monitoring (MRM) mode using positive electrospray ionization (ESI). The methods were validated over the concentration range of 0.2–50ng/mL for F-VCR and 0.5–400ng/mL for T-VCR, respectively. Inter- and intra-day precision (RSD%) were ≤4.7% for F-VCR and ≤9.8% for T-VCR, respectively. The accuracies were between −2.3 and 9.1% for F-VCR and between −3.2 and 6.9% for T-VCR, respectively. The extraction recovery and the matrix effect were investigated. The methods were successfully applied to the pharmacokinetic study of VSLI in Chinese subjects with lymphoma.